Laterally loaded piles in permafrost - Nixon, J. F. (Derick) (Canadian Geotechnical Journal, 1984)
A theory for the design of laterally loaded piles in permafrost is presented. The approach is valid for icy soils or ice, where secondary creep displacements will be responsible for the majority of the soil strain under sustained load. Initially, the paper studies in some detail the response of a short, rigid pile embedded in a nonlinear viscous medium. The concept of a flexible elastic pile in a viscous continuum is then introduced, and a relatively straightforward numerical procedure must be introduced to obtain a solution. Once the limiting or design ground surface displacement rate is established by the designer, the paper shows how a typical chart relating lateral pile load to average ground temperature can be prepared.The available (but limited) data base is reviewed for field pile load tests carried out in the early 1970's in Inuvik, N.W.T. and some laboratory model pile tests carried out in connection with this study. Using available long-term secondary creep data for ice and icy silts, predictions for the lateral creep response of piles can be carried out. Agreement between prediction and observation is certainly encouraging and points the way to further research and field testing in this area. Finally, the paper briefly discusses the resistance of rigid fixed-headed piles to lateral loads, and the resistance of a pile in permafrost to the application of a pure moment. Key words: lateral piles, permafrost, creep, model, field tests.